Being a heritage speaker matters: the role of markedness in subject-verb person agreement in Italian - Di Pisa, Grazia; Pereira Soares, Sergio Miguel; Rothman, Jason; Marinis, Theodoros (Frontiers in Psychology, 2024)
This study examines online processing and offline judgments of subject-verb person agreement with a focus on how this is impacted by markedness in heritage speakers (HSs) of Italian. To this end, 54 adult HSs living in Germany and 40 homeland Italian speakers completed a self-paced reading task (SPRT) and a grammaticality judgment task (GJT). Markedness was manipulated by probing agreement with both first-person (marked) and third-person (unmarked) subjects. Agreement was manipulated by crossing first-person marked subjects with third-person unmarked verbs and vice versa. Crucially, person violations with 1st person subjects (e.g., io *suona la chitarra “I plays-3rd-person the guitar”) yielded significantly shorter RTs in the SPRT and higher accuracy in the GJT than the opposite error type (e.g., il giornalista *esco spesso “the journalist go-1st-person out often”). This effect is consistent with the claim that when the first element in the dependency is marked (first person), the parser generates stronger predictions regarding upcoming agreeing elements. These results nicely align with work from the same populations investigating the impact of morphological markedness on grammatical gender agreement, suggesting that markedness impacts agreement similarly in two distinct grammatical domains and that sensitivity to markedness is more prevalent for HSs.